2008
DOI: 10.1080/00926230701636163
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function and Its Associations with Number of Children, Pregnancy, and Relationship Satisfaction

Abstract: Associations between number of children, pregnancy, and overall relationship satisfaction were explored in a population-based sample of 2081 women, aged 33-43 years. Multiparous women had less orgasm problems compared to nulliparous women. Nulliparous women had more pain problems and were sexually less satisfied compared to women with children, regardless of the number. Women pregnant with the first child had fewer pain problems compared to a matched nonpregnant control and were sexually more satisfied. Being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 50 publications
5
64
3
5
Order By: Relevance
“…The existing research on rela tionship satisfaction and living with children has been conflicting. Some studies found relationship satisfaction was negatively related to living with chil dren (Erlandsson et al, 2010), while others found no significant relationship (Mitnick, 2009;Witting et al, 2008). Our research was consistent with the research that found no significant effects of living with children on relationship satisfaction.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The existing research on rela tionship satisfaction and living with children has been conflicting. Some studies found relationship satisfaction was negatively related to living with chil dren (Erlandsson et al, 2010), while others found no significant relationship (Mitnick, 2009;Witting et al, 2008). Our research was consistent with the research that found no significant effects of living with children on relationship satisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…This could be explained because children and a spouse are additional stressors in women's lives, which might have an impact on relationship satisfaction. However, other research shows that number of children has no effect on relationship satisfaction (Witting et al, 2008). A metaanalysis compar ing relationship satisfaction among couples with children and couples without children found that relationship satisfaction decreased in couples who had children, but this may be more indicative of relationship changes over a time span than parent hood (Mitnick, Heyman, & Smith Slep, 2009).…”
Section: Relationship Satisfactionmentioning
confidence: 95%
See 1 more Smart Citation
“…As mentioned previously, sexual dysfunction is often associated with sexual guilt and sexual anxiety. This relationship becomes all the more concerning given that, in women especially, decreased sexual functioning and dissatisfaction have been associated with decreased relationship (Witting et al, 2008) and marital satisfaction (Brezsnyak & Whisman, 2004;Trudel & Goldfarb, 2010). As rates of divorce among Muslims in North America rise (Macfarlane, 2012), understanding a possible role of sexual guilt and anxiety in marital discord could help counter this trend.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…As mentioned previously, sexual dysfunction is often associated with sexual guilt and sexual anxiety. This relationship becomes all the more concerning given that, in women especially, decreased sexual functioning and dissatisfaction have been associated with decreased relationship (Witting et al, 2008) and marital satisfaction (Brezsnyak & Whisman, 2004;Trudel & Goldfarb, 2010). As rates of divorce among Muslims in North America rise (Macfarlane, 2012), understanding a possible role of sexual guilt and anxiety in marital discord could help counter this trend.…”
Section: Practice Implicationsmentioning
confidence: 99%